Busulfan-Based Intensified Myeloablative Conditioning Regimen Allogeneic Hematopoietic Cell Transplantation for Juvenile Myelomonocytic Leukemia-Single Center Study - Wang, Yun; Sun, Ruijuan; Zhao, Yanli; Wei, Zhijie; Xiong, Min; Liu, Deyan; Lu, Peihua; Lu, Yue (Blood, 2024)
Background: Juvenile myelomonocytic leukemia (JMML) is a life-threatening myeloproliferative neoplasm, allogeneic hematopoietic stem cell transplantation(allo-HSCT) is the only curable method for it, but disease recurrence and graft rejection are major causes of treatment failure, thus,new conditioning regimen are needed to improve the survival outcomes in patients with JMML. Method:We retrospectively analyzed 14 patients who diagnosis with JMML(according to 2022 WHO) and received Busulfan(BU)-based intensified Myeloablative conditioning regimen(MAC) allo-HSCT,evaluated its prognosis.Results: 9 males and 5 females; the median age were 4 years (10 months to 10 years); 8 cases with PTPN1 mutation positive, 3 cases NF1 mutation positive, 1 NRAS , 1 KRAS, 1 CBL; 5 of them with another gene mutation abnormality, 3 of them with three or more gene mutation abnormalities. 3 patients had chromosome -7. 5 of them had hepatosplenomegaly.Donor type: 9 patients received related haploidentical donors, 4 received matched sibling donors, and 1 received unrelated matched donors. The median proportion of blast cells in bone marrow before transplantation was 11% (range:3.4-21.2). 9 patients received demethylating drug treatment before transplantation.All patients received BU-based intensified MAC, Seven patients received Decitabine/Cytarabine (Ara-c) /BU/ Cyclophosphamide (Cy) or Fludarabine (FLU) /Melphalan (MEL) / ATG (n=7), 3 cases received FLAG + BU/Cy or FLU /ATG (n=3); 4 received Ara-c/BU/CY/MEL /ATG (n=4). All patients achieved stem cell engraftment, the median neutrophils and platelet engraftment times were 15 (range:10-18) days and 12 (range:9-87) days respectively. Six patients developed II-IV aGVHD, three patiens developed mild cGVHD, and two developed severe cGVHD. Eleven patients survived, the median survival time were 36 (12-108) months; the 5-year overall survival(OS) and relapse-free survival(RFS) were 78.6±11.1% and 78.6±11.1%, respectively, and the 5-year cumulative incidence of relapse(CIR) was 15.4±10.0%; the 5-year non relapse mortality(TRM) was 8.1±6.9%. Three patients died until last follow-up time, two of whom died of disease recurrence (six months and eight months after transplantation, respectively), and one died of aGVHD after transplantation three months. Conclusion: Allo-HSCT with busulfan-based intensified myeloablative conditioning regimen for JMML achieved all stem cell engraftment, lower CIR and encouraging survival. No relevant conflicts of interest to declare.